Nilai Pengelolaan LAR, DRR, Activity Ratio Terhadap Rentabilitas di Masa Pandemi Covid -19 Pada LPD Desa Adat Lemukih, Kecamtan Sawan - nikadek ayu trisnadewi; I Putu Agus Adnyana; Ni Luh Sri Kasih (Universitas Pendidikan Ganesha, 2022)
Analysis of Loan to Assets Ratio Management, Deposit Risk Ratio and Activity Ratio to Profitability in 5 LPD in Buleleng Regency. The purpose of this study was to determine the management of Loan to Asset Ratio, Deposit Risk Ratio and Activity Ratio to Rentabilitas. This study uses Financial Statement data for 5 years 2015-2020.The object of research is the Village Credit Institution (LPD) in Buleleng . The sample of this research is 5 LPD in Buleleng Regency which are the target of the place where the researcher works. The data that has been collected was analyzed using data analysis techniques with multiple regression, determination test and significance test. The results of the study found that the Loan to Asset Ratio, Deposit Risk Ratio and Activity Ratio had a simultaneous or joint effect on profitability so that it could be indicated by the significance level of less than 5%. The Deposit Risk Ratio partially positive effect on Rentability, which means that the more The higher the Deposit Risk Ratio, the higher the profitability of the LPD. Management of Activity Ratio has an effect on Rentability. The positive effect shown by the Activity Ratio indicates that the higher the risk of assets in the management of the LPD by the activity ratio, the lower the level of capital so that it has an impact on the Rentability of the LPD which we can see in the value of its activity. Keywords: LAR, DRR ,AR , Profitability